Annual Plan Progress Review of Haryana 1969-70 - Planning Commission (Planning Commission, 1971)
Before re-organisation most of the development efforts were concentrated in the new Punjab State and the areas now constituting Haryana were very much neglected. This created a situation of backward economy which needed drastic measures to improve the socio-economic conditions of the people of the new State. In late 1966 when Haryana was formed, a major part of the expenditure of the annual plan for 1966-67 had already been incurred and what was inherited from composite Punjab was a meagre share determined on the basis of pro-rata distribution of outlays.
Economic and Statistical Organisation, Planning Department, Haryana